Peran Pengetahuan dalam Memengaruhi Niat Berhenti Konsumsi Boba Kajian Konten TikTok @farhanzubedi - Widyatna, Tazkiya Syifa Azaria; Gracia, Amanda Bunga; Al Husain, Andi Hasan (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Boba drinks are drinks that are being sold in the market, but these drinks have a high sugar content, as well as calories that can cause several serious diseases, one of which is diabetes. So there is a need for health education to the public, one of which is through a social media platform, namely Tiktok. The purpose of this study is to see the effect of tiktok content on diabetes @farhanzubedi on knowledge, knowledge on intention to stop consuming boba, tiktok content on diabetes @farhanzubedi on intention to stop consuming boba, and tiktok content on diabetes @farhanzubedi on intention to stop consuming boba by Indonesian students through knowledge. Researchers use quantitative research methods by distributing questionnaires online to obtain data, then path analysis is used as a data analysis technique assisted by the SPSS application as a test tool. The results showed that @farhanzubedi's diabetes content affects knowledge among Indonesian students, knowledge affects intention to stop consuming boba, @farhanzubedi's diabetes content affects intention to stop consumption among Indonesian students, and @farhanzubedi's diabetes content affects intention to stop consuming boba through knowledge among Indonesian students.